Strengthening Songket Palembang Business - Zulfikar Ikhsan Pane; Rosida Simatupang; Yosaphat Danis Murtiharso (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Songket is a traditional fabric from Palembang that remains in high demand. Over time, its motifs have become increasingly diverse, even incorporating elements from other cultures. Unfortunately, sales have been hampered, so this project sought to strengthen these challenges and address them. This project was conducted through an interview with Songket business owner, Mr Fikri, on September 15, 2024, and a visit to the industry center. Results revealed a decline in sales due to change of Sultan Mahmud Badaruddin International Airport's status as a domestic airport, in addition to the impact of the Covid-19 pandemic. Suggestions were given to increase online sales and propose to the local government for change domestic airport to an international airport status